GRASPs in Golgi Structure and Function - Zhang, Xiaoyan; Wang, Yanzhuang (Frontiers in Cell and Developmental Biology, 2016)
The Golgi apparatus is a central intracellular membrane organelle for trafficking and modification of proteins and lipids. Its basic structure is a stack of tightly aligned flat cisternae. In mammalian cells, dozens of stacks are concentrated in the pericentriolar region and laterally connected to form a ribbon. Despite extensive research in the last decades, how this unique structure is formed and why its formation is important for proper Golgi functioning remain largely unknown. The Golgi ReAssembly Stacking Proteins, GRASP65 and GRASP55, are so far the only proteins shown to function in Golgi stacking. They are peripheral membrane proteins on the cytoplasmic face of the Golgi cisternae that form trans-oligomers through their N-terminal GRASP domain, and thereby function as the “glue” to stick adjacent cisternae together into a stack and to link Golgi stacks into a ribbon. Depletion of GRASPs in cells disrupts the Golgi structure and results in accelerated protein trafficking and defective glycosylation. In this minireview we summarize our current knowledge on how GRASPs function in Golgi structure formation and discuss why Golgi structure formation is important for its function.